2014 47th Hawaii International Conference on System Sciences 2014
DOI: 10.1109/hicss.2014.389
|View full text |Cite
|
Sign up to set email alerts
|

Why Aren't the Stars Aligned? An Analysis of Online Review Content and Star Ratings

Abstract: Consumer-generated product evaluations posted on online retailer or third party web-sites have been shown to increase buyer trust and aid consumer decision making. These online reviews typically have two components: star ratings and review text. This can communicate a complex, conflicting message to consumers, as the text of a review carries more nuance than what can be communicated through a simple numerical score. Misalignment between the star rating and the text can lead to increased consumer cognitive proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…This query can be qualitative, quantitative, or both. Qualitative feedback includes textual information, while quantitative feedback is given using a predefined scale level (Chevalier and Mayzlin 2006;Mudambi et al 2014).…”
Section: Design Characteristics Of Feedback Mechanisms On Digital Plamentioning
confidence: 99%
See 1 more Smart Citation
“…This query can be qualitative, quantitative, or both. Qualitative feedback includes textual information, while quantitative feedback is given using a predefined scale level (Chevalier and Mayzlin 2006;Mudambi et al 2014).…”
Section: Design Characteristics Of Feedback Mechanisms On Digital Plamentioning
confidence: 99%
“…Moreover, such dysfunctional effects extend beyond the mechanism of eBay. For instance, manipulations such as inconsistent feedback occur within other feedback mechanisms (e.g., Amazon, TripAdvisor and Booking.com) (Fazzolari et al 2017;Mayzlin et al 2014;Mudambi et al 2014). These dysfunctional feedback mechanisms may lead to a decline in users' motivation to provide feedback (McDonald and Slawson 2002) and, as a result, may cause a negative attitude towards feedback (Abramova et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, in this paper, we consider the presence of a possible misalignment between the review text and the review score. As noticed in [1], such a misalignment could lead to the increase of the consumer cognitive processing costs, to sub-optimal purchase decisions, and, ultimately, to neutralize the utility of the review site. Here, we approach the issue under a different perspective and with the aim of positively exploiting hidden information that may exist, for those reviews featuring the disagreement between the text and the score.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is a strong correlation between high star ratings and helpful reviews. Another study has investigated how misalignment between the star rating and the textual content of the review can lower the overall helpfulness of the review [81]. It found that misalignment between star rating and review text often occurs in reviews of experience goods and in reviews with high star ratings.…”
Section: Categorymentioning
confidence: 99%